Program Kemiskinan dan Perkembangan Intelegensi - Jannah, Aulia Azfa; Ma’bud, Mochamad Ma’rifatul; M, Marshella (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Poverty is one of the most pressing social problems in various countries. Not only does it impact the quality of life in general, poverty also has significant implications for the intelligence development of children, who are exposed to this condition from an early age. Various studies show that children from poor families tend to have lower intelligence scores compared to children from families with better economic status. This program aims to identify and implement interventions that can help improve the intelligence development of children from poor families. The main focus is on increasing access to quality education, adequate nutrition, and an environment that supports cognitive development.